Building and sustaining collaboration in cross sector e-learning development - Timmons, Stephen; Wharrad, Heather; Vezyridis, Paraskevas; Randle, Jacqueline; Lymn, Joanne; Bath-Hextall, Fiona (IGI Global, 2010)
This chapter will focus on the process of building and sustaining collaborative reusable e-learning object development across three educational sectors, Higher Education (HE), the UK National Health Service (NHS) and Further Education (FE) Colleges, using the LOLA project as a case study. A qualitative evaluation of ‘process’ ran alongside the entirety of the LOLA project. This chapter reports the findings of this qualitative research, and analyses how collaboration was achieved between the diverse institutions who were project partners. The strengths of this approach included the commitment of the team members to collaboration, while practical challenges included the location of the team members, but also wider issues in the institutions involved, and in particular, the role of the Media Developer and the perception of it by other team members.